The desalination of salt water fix for irrigation by electrodialysis and its effects on the germination, growth and seed yield of wheat ( Triticum durum Desf. Var. Karim) (International Journal of Irrigation and Water Management, 2014)
Morocco is characterised by a semi-arid climate and by unlimited conventional fresh water especially underground water. Electrodialysis experiment to desalinise water for irrigation was conduced on underground water from the north of Morocco. The effects of the use of desalted water on the germination and growth and seed yield of wheat were monitored to determine the best yield from use of desalted water for irrigation of wheat.